2024
DOI: 10.1111/epi.17899
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic changes in adults with status epilepticus: A human case–control study

Aurélie Hanin,
Céline Chollet,
Sophie Demeret
et al.

Abstract: ObjectiveStatus epilepticus (SE) is a life‐threatening prolonged epileptic seizure that affects ~40 per 100 000 people yearly worldwide. The persistence of seizures may lead to excitotoxic processes, neuronal loss, and neuroinflammation, resulting in long‐term neurocognitive and functional disabilities. A better understanding of the pathophysiological mechanisms underlying SE consequences is crucial for improving SE management and preventing secondary neuronal injury.MethodsWe conducted a comprehensive untarge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…However, it is clear that the blood metabolome of someone experiencing status epilepticus is significantly different from someone with control epilepsy patients. 51 Future work need to validate identified biomarkers externally in an independent cohort. It will also be important to explore the applicability of the NMR blood test in identifying other AE subtypes, seronegative AE patients and whether the AE metabolomic signature might be used to predict the persistence of AE.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is clear that the blood metabolome of someone experiencing status epilepticus is significantly different from someone with control epilepsy patients. 51 Future work need to validate identified biomarkers externally in an independent cohort. It will also be important to explore the applicability of the NMR blood test in identifying other AE subtypes, seronegative AE patients and whether the AE metabolomic signature might be used to predict the persistence of AE.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent animal research demonstrated that subchronic administration of palmitoylethanolamide markedly diminished seizure intensity and fostered neuroprotection, which can also modulate plasma and hippocampal endocannabinoid and eicosanoid levels in systemic KA-injected mice ( 12 ). An investigation into metabolomic alterations in adult status epilepticus (SE) patients showed that metabolic dysregulation primarily impacted amino acid metabolism, pyrimidine metabolism and lipid homeostasis ( 13 ). The existing association between epilepsy and plasma liposomes primarily arises from observational studies characterized by limited sample sizes and numerous confounding variables.…”
Section: Introductionmentioning
confidence: 99%